TINGKAT KESEHATAN KOPERASI PEGAWAI NEGERI WERDHI GUNA KARANGASEM - Sri Laksmi Dewi; I Ketut Mustika (Journal of Applied Management Studies, 2021)
This study aims to analyze the Health Level Assessment of the Werdhi Guna Civil Servant Cooperative 2015 - 2019 based on the capital aspect, productive asset quality aspect, management aspect, efficiency aspect, liquidity aspect, independence and growth aspect, and cooperative identity aspect; This research is a type of quantitative descriptive research. The subjects of this study were the Civil Servant Cooperative Werdhi Guna Karangasem; The object evaluated in this study is the cooperative's health level in terms of capital, productive asset quality, management aspect, efficiency aspect, liquidity aspect, independence and growth aspect, and cooperative identity aspect. Data collection in this study was carried out by distributing questionnaires and documentation. Data analysis is based on the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 06/Per/Dep.6/IV/2016. The results showed: (1) The Health Level of the Werdhi Guna Karangasem Civil Servant Cooperative in 2015-2019 in terms of capital aspects, productive asset quality aspects, management aspects, efficiency aspects, liquidity aspects, independence and growth aspects, and cooperative identity aspects were in the predicate quite healthy